The Effect of Understanding Taxation Regulations, Tax Rates, Tax Sanctions, Tax Socialization, Fiscus Services and Online Services on The Level of Compliance with MSME Taxpayers - Asih Machfuzhoh; Refi Pratiwi (FEB Universitas Sultan Ageng Tirtayasa, 2021)
The tax function is very important for development. The largest contributor to state income is taxes. MSMEs is a business group with a sizeable number in Indonesia. The large number of MSMEs actors has made the Government pay serious attention to the development of MSMEs. This study aims to examine the effect of understanding tax regulations, tax rates, tax sanctions, tax socialization, tax services and online services on the level of compliance of general public taxpayers. The population in this study is MSMEs in Cilegon. The sample of this research is MSMEs in Cilegon. The research methodology stage began by collecting data through distributing questionnaires to MSMEs actors in the Cilegon area, followed by data analysis. This research data is primary, the data were analyzed using validity and reliability tests and multiple linear regression.